2019
DOI: 10.1021/acs.nanolett.9b00596
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Nanoscale Skyrmions in SrIrO3/SrRuO3 Bilayers

Abstract: Skyrmion imaging and electrical detection via topological Hall (TH) effect are two primary techniques for probing magnetic skyrmions which hold promise for next-generation magnetic storage. However, these two kinds of complementary techniques have rarely been employed to investigate the same samples. We report the observation of nanoscale skyrmions in SrIrO3/SrRuO3 (SIO/SRO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
141
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(151 citation statements)
references
References 36 publications
8
141
2
Order By: Relevance
“…With these differences, we are confident that the current result represents a novel strategy to engineer the THE in SrRuO 3 . It is interesting to note that using magnetic force microscope (MFM), some studies observe the nanoscale skyrmion in the ultra-thin SrRuO 3 heterostructures 13,16,39 , and therefore attributed the observed THE to the formation of skyrmion. We speculate that this also forms a plausible explanation for our result since our sample holds all essential ingredients required to host Skyrmion: broken inversion symmetry, strong spin-orbital coupling and reduced magnetization.…”
Section: Discussionmentioning
confidence: 99%
“…With these differences, we are confident that the current result represents a novel strategy to engineer the THE in SrRuO 3 . It is interesting to note that using magnetic force microscope (MFM), some studies observe the nanoscale skyrmion in the ultra-thin SrRuO 3 heterostructures 13,16,39 , and therefore attributed the observed THE to the formation of skyrmion. We speculate that this also forms a plausible explanation for our result since our sample holds all essential ingredients required to host Skyrmion: broken inversion symmetry, strong spin-orbital coupling and reduced magnetization.…”
Section: Discussionmentioning
confidence: 99%
“…In SRO epitaxial heterostructures hosting a fine balance between el-el correlation and SOC, interfacial inversion-symmetry-breaking can activate the Dzyaloshinskii-Moriya interaction (DMI). As a consequence, magnetic skyrmions and chiral magnetic domains can be stabilized and embedded in a ferromagnetic matrix (32)(33)(34)(35)(36). The resultant inhomogeneity in real-space Berry curvature inevitably induces a superposition of THE and AHE signals ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The resultant inhomogeneity in real-space Berry curvature inevitably induces a superposition of THE and AHE signals ( Fig. 1, A (32)(33)(34)(35). Soon after the discoveries of THE in SRO heterostructures, an alternative interpretation based on spatial inhomogeneity in AHE and k-space Berry curvature was proposed (37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the density of the skyrmions is proportional to the component of THE in AHE signal. [ 3,10,39 ] These discussions imply that the magnetic skyrmion should be responsible for the THE in SRO/BFO heterostructures. We noted that the inhomogeneous thickness (thickness difference of 0.5 nm) have been used for interpreting the anomaly in AHE.…”
Section: Figurementioning
confidence: 99%